2008
DOI: 10.1152/ajpcell.00287.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia increases the gain of excitation-contraction coupling in guinea pig ventricular myocytes

Abstract: Shutt RH, Howlett SE. Hypothermia increases the gain of excitation-contraction coupling in guinea pig ventricular myocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 40 publications
2
30
1
2
Order By: Relevance
“…Commonly, as cardiac cell contraction is in part an active energetic process, hypothermia might be expected to reduce the cardiac contractile state. However, Shutt and Howlett [6] described that paradoxical experiments with experimental animals such as guinea pig, rabbit, canine and ferret, have shown an increase in contractility and the gain of excitation-contraction coupling with cooling. They [6] also described that many studies using experimental animals had shown that cooling increases action potential duration, and slowed the rate of Na/Ca exchange in cardiac cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, as cardiac cell contraction is in part an active energetic process, hypothermia might be expected to reduce the cardiac contractile state. However, Shutt and Howlett [6] described that paradoxical experiments with experimental animals such as guinea pig, rabbit, canine and ferret, have shown an increase in contractility and the gain of excitation-contraction coupling with cooling. They [6] also described that many studies using experimental animals had shown that cooling increases action potential duration, and slowed the rate of Na/Ca exchange in cardiac cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, Shutt and Howlett [6] described that paradoxical experiments with experimental animals such as guinea pig, rabbit, canine and ferret, have shown an increase in contractility and the gain of excitation-contraction coupling with cooling. They [6] also described that many studies using experimental animals had shown that cooling increases action potential duration, and slowed the rate of Na/Ca exchange in cardiac cells. Hypothermia also increases the open probability of cardiac sarcoplasmic reticulum Ca2+ release channels, and reduces the activity of sarcoplasmic reticulum Ca2+ ATPase but increases sarcoplasmic reticulum Ca2+ load in cardiac cells [6] .…”
Section: Discussionmentioning
confidence: 99%
“…17,18,34 Alternatively, decreasing temperature also increases RyR-Po, 17 as well as fractional and net Ca release from RyR. 17,18, 40 We contend that these 2 processes combined determine the occurrence of triggered activity. This is manifest in the biphasic nature of the mSCR slope and DAD amplitude (Figure 2B), both of which are directly related to triggered activity occurrence.…”
Section: Mechanisms Underlying the Temperature-dependent Effects Of Hmentioning
confidence: 98%
“…Se sabe que las propiedades electrofisiológicas de las células cardíacas se ven influenciadas por la temperatura Bers 1989, Shutt andHowlett 2008]. En consecuencia, el proceso de propagación de la excitación eléctrica en el miocardio puede verse afectado, en condiciones normales o durante las arritmias, por los cambios de temperatura del tejido.…”
Section: Electrofisiología Experimental Y Temperaturaunclassified
“…Al contrario de lo que ocurre con la hipotermia, la hipertermia moderada acorta el potencial de acción e incrementa la velocidad de conducción [Tachibana et al 1999, Simmers et al 1995, Nygren et al 2003]. …”
Section: Efectos a Nivel Celularunclassified